Formulation and Evaluation of Taste Masked Tablet of Sodium Feredetate: Taste Masking Approach (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: sodium feredetate; chewable tablet; taste masking; #x3B2; -cyclodextrin; electronic tongue